New records of mites of the Heterostigmata (Acari: Prostigmata) associated with insects from Golestan Province, northern Iran - Vahid Rahiminejad; Hamidreza Hajiqanbar (Persian Journal of Acarology)
Moderate and humid region in north of Iran is home to a rich arthropod fauna, yet the mite fauna of Golestan province, with moderate Caspian climate, is poorly studied systematically. In this study, we conducted a faunistic study on heterostigmatic mites (Acari: Prostigmata: Eleutherengonides) associated with insects in Golestan Province. We used both day and overnight sampling methods to capture host insects in sampling sites. Thirteen species of seven heterostigmatic families were identified: Dolichocybidae (one species), Caraboacaridae (one species), Trochometridiidae (one species), Neopygmephoridae (three species), Pygmephoridae (three species), Scutacaridae (two species) and Microdispidae (two species). The genus Formicomotes and subgenus Imparipes (Sporichneuthes) are new records for Iran and Asia, respectively. Beyond this, 13 new insect host records are reported for heterostigmatic mites. Finally, the world distribution of the recovered mites is reviewed.